Electrochemical Behaviours of 4,4’-Methylenedianiline in Non-Aqueous Media on a Platinum Electrode Surface - Demir Mulazimoglu, Aysen; Yilmaz, Ecir (Asian Journal of Chemistry, 2012)
Electrochemical behaviours of 4,4'-methylenedianiline were investigated by cyclic voltammetry, differential pulse voltammetry and electrochemical impedance spectroscopy on a platinum electrode surface. The platinum working electrode surface was modified with 4,4'-methylenedianiline in acetonitrile containing 100 mM tetrabutylammonium tetrafluoroborate using 100 mV s-1 scan rate from 0.0 mV to +1600 mV potential range with 30 cycles. In differential pulse voltammetry experiments, the potential range was from 0.0 mV to +1000 mV. The presence of 4,4'-methylenedianiline at the platinum electrode surface was characterized by cyclic voltammetry and electrochemical impedance spectroscopy.